A comparative study of the firing shrinkage properties of the process temperature control rings - Punsukmtana, Lada; Vorasapavit, Chantarat; Saephoo, Siriwan; Balsri, Chatchai (Bulletin of Applied Sciences, 2022)
A process temperature control ring was developed from talc, magnesium carbonate, barium carbonate, iron oxide, kaolin, and quartz. The ring is formed by dry pressing method into a 2.5 cm diameter ring with the density 1.8 g/cm3. The ring had the firing shrinkage after fired at 960°C, 1100°C, 1140°C, and 1200 °C varied in the range 2.21-9.98 % with the standard deviation varied in the range 0.00-0.06. In this study, the properties of the ring were statistical analyzed. It was found that an increasing temperature resulted in an increasing firing shrinkage but had no effect on the standard deviation values. The study also presented the comparative properties of the ring with the one available in the market in terms of the average firing shrinkage, the standard deviation and the change of the shrinkage with temperature.